Bibliometric visualization and analysis of research on health promotion involving Taijiquan— a comparison and outlook based on core Chinese and English literature - Zhang, Chenchen; Kang , Ziye; Zhang, Jianwei (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details